Impact of the body mass index on the intensive care outcome of (poly-)traumatized patients - Schnabel, Timon Marvin; Scherer, Natalie; Böhmer, Andreas B.; Lefering, Rolf; Gerbershagen, Mark Ulrich (Frontiers in Anesthesiology, 2026)
PurposeThe increasing prevalence of obesity poses significant challenges to intensive care medicine, particularly in trauma care. The “obesity paradox”, suggesting enhanced survival in overweight individuals, remains controversial. The study aimed to investigate the association between Body Mass Index and intensive care outcomes in severely injured patients.MethodsA retrospective matched 1:2:1 set analysis with n = 192/384/192 patients was conducted using data from the TraumaRegister DGU®. A total of 5,766 patients admitted to intensive care were included and categorized into three BMI groups: underweight (≤20 kg/m2), normal weight/overweight (20.1–29.9 kg/m2), and obese (≥30 kg/m2). The application of World Health Organization classification was precluded on statistical grounds. A subgroup of polytraumatized patients (n = 272) was separately analyzed. Outcomes included the duration of mechanical ventilation, ICU stay, organ failure, and in-hospital mortality.ResultsBMI was positively associated with organ failure, especially cardiac (p = 0.001) and pulmonary failure (p = 0.001). The mortality rate was twice as high for obese patients as for underweight patients in the matched cohort [Group III: 10.4%; Group I: 5.2%; p (linear trend) = 0.025]. Ventilation time increased significantly with higher BMI (p = 0.012).ConclusionIn this cohort, there was an absence of evidence to support the notion of an “obesity paradox”. Overweight and obesity were not associated with improved survival and were instead linked to less favorable intensive care outcomes following severe trauma, although absolute differences in mortality were modest.Trial registrationID 2014-021.